Silent Legitimacy: How Breadwinner Norms and Communicative Accommodation Shape Food Decision-Making in Low-Income Households Through a Muted Group Theory Lens - Dhea Dasa Cendekia Zairin; Annisa Utami Seminar; Dyah Retna Puspita (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Gendered communication inequality in low-income households is often obscured within domestic activities, despite its critical role in shaping household food habits. Women bear the primary responsibility for food provision; however, their voices and knowledge are frequently marginalized due to male dominance. Under conditions of economic constraint, food-related decisions tend to reflect power relations rather than nutritional considerations. This study aims to examine socio-economic conditions, forms of power relations in gendered communication, food decision-making processes, and food habits within low-income households in Banjar Regency, South Kalimantan. The research employs a qualitative approach with a multiple-case study design. Data were collected through in-depth interviews, observation, and documentation, and were analyzed thematically using NVivo 12 Pro. Muted Group Theory serves as the analytical lens to explore patterns of domination, subordination, acceptance, and negotiation that emerge in household food decision-making. The findings reveal that unequal food decisions are not solely a response to economic limitations, but are also shaped by communication practices embedded within gender-based power relations in low-income households. This study highlights the importance of gender-equitable interventions to promote healthier and more sustainable food practices.